2019
DOI: 10.1177/0300060519860324
|View full text |Cite
|
Sign up to set email alerts
|

Re-evaluation of the value of sperm morphology in classical in vitro fertilization in a Northeastern Chinese population

Abstract: Objective This study aimed to re-evaluate the clinical value of a 4% cut-off threshold of sperm morphology in in vitro fertilization (IVF) in a cohort of a Northeastern Chinese population. Methods A total of 375 IVF cycles that met strict inclusion criteria were included. These cycles were conducted with semen analysis and oocyte fertilization. A total of 188 embryo-transferred cycles proceeded. According to sperm morphology, 375 cycles were divided into group 1 (329 cycles, <4% normal sperm morphology rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 20 publications
(31 reference statements)
0
9
0
Order By: Relevance
“…In specimens with otherwise normal count and motility, poor morphology may itself be a determinant in deciding whether or not to proceed with ICSI. When the percentage of sperm with normal morphology is <4%, fertilization with IUI and IVF is poor, and ICSI should be preferred [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In specimens with otherwise normal count and motility, poor morphology may itself be a determinant in deciding whether or not to proceed with ICSI. When the percentage of sperm with normal morphology is <4%, fertilization with IUI and IVF is poor, and ICSI should be preferred [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The reference range for normal SM moved from 30% in 1992 to 14% in 1999 and finally to 4% in 2010. 7 Although some laboratories do not consider SM quite important, 8 several studies have demonstrated that poor sperm quality and SM are associated with higher incidence of aneuploid embryos, suggesting that the meiotic events occurring during fertilization could impact on the distribution of chromosomes. 9,10 Moreover, comparing couples which men have normal SM < 4% and those with SM ≥ 4% in in vitro fertilization (IVF) cycles, a significant reduction in fertilization rates was found in the first group, despite the lack of significant differences on clinical and neonatal outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The reference range for normal SM moved from 30% in 1992 to 14% in 1999 and finally to 4% in 2010 7 . Although some laboratories do not consider SM quite important, 8 several studies have demonstrated that poor sperm quality and SM are associated with higher incidence of aneuploid embryos, suggesting that the meiotic events occurring during fertilization could impact on the distribution of chromosomes 9,10 …”
Section: Introductionmentioning
confidence: 99%
“…www.eCERM.org requisite factor for the successful use of assisted reproductive technology (ART) [16,17]. Our results indicated that abnormal sperm mainly showed changes in head morphology, and that amorphous-head and tapered spermatozoa were more common in the abnormal morphology group.…”
Section: Discussionmentioning
confidence: 70%
“…Sperm morphology is the most relevant parameter in conventional semen analysis for predicting fertilization potential [ 11 , 15 ], a prerequisite factor for the successful use of assisted reproductive technology (ART) [ 16 , 17 ]. Our results indicated that abnormal sperm mainly showed changes in head morphology, and that amorphous-head and tapered spermatozoa were more common in the abnormal morphology group.…”
Section: Discussionmentioning
confidence: 99%